Changes in the status of waqf: Understanding of the Community Living in the Santiong Cemetery Land Waqf - Umasugi, Nirwan; Nasim, Abu Sahman (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2025)
This study investigates the contested status of waqf land designated for the Santiong Village Public Cemetery (TPU), which has been occupied by community members for housing, creating a conflict over its intended use. The research aims to analyze the legal status of this waqf land from an Islamic law perspective and to assess the resident community's understanding and perception of its function and empowerment principles. Using a quantitative method, data was collected via questionnaires distributed to a sample of 50 residents living on the waqf land. The research reveals two primary issues. First, the legal status of the waqf land is precarious; it lacks an official certificate from the Land Agency and relies solely on a Notary Deed held by the An-Nur Foundation, the acting nazhir (manager). Second, community understanding of waqf principles is low, with a majority of residents (66%) not providing empowerment benefits to the nazhir5. Despite these legal and social challenges, the study concludes that the waqf land possesses significant potential for future development. This potential is based on indicators such as the positive character of some respondents toward waqf and the prospective economic empowerment of the community.